2020
DOI: 10.1177/0963689720943613
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA MTO1 Inhibits the Proliferation and Invasion of Ovarian Cancer Cells Through the miR-182-5p/KLF15 Axis

Abstract: Circular RNAs (circRNAs) are a novel class of endogenous noncoding RNAs and have been shown to play important roles in a variety of physiological processes. Recently, dysregulation of circRNAs has been identified in many types of cancers. In this study, we analyzed the expression profile and biological functions of circMTO1 in ovarian cancer. We demonstrated that circMTO1 was downregulated in ovarian cancer tissues and cell lines. Upregulation of circMTO1 inhibited proliferation and invasion of ovarian cancer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 41 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…15 Also, circMTO1 was considered as a biomarker for OC, which could suppress OC proliferation and invasion via regulating miR-182-5p/KLF15. 16 Hence, elucidating the role of circRNA in cancers can provide us with a deeper understanding of the tumorigenesis mechanism, thus providing a new direction for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…15 Also, circMTO1 was considered as a biomarker for OC, which could suppress OC proliferation and invasion via regulating miR-182-5p/KLF15. 16 Hence, elucidating the role of circRNA in cancers can provide us with a deeper understanding of the tumorigenesis mechanism, thus providing a new direction for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…13 Circ-MTO1 suppresses ovarian cancer cell progression and metastasis by sponging miR-182-5p and upregulating KLF15 expression. 14 In the present study, miR-510-5p was identified as a target for circ-ELF2 among seven candidate miRNAs. MiR-510-5p was previously identified as a tumor-suppressive miRNA in several human malignancies, such as renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 58%
“…Further optimization of benzimidazole turns out a dimeric benzimidazole and bisbenzimide compound, targaprimir-96, which shows a favorable pharmacokinetics profile and is effective at releasing tumor burden in a triple-negative breast cancer xenograft mouse model [65]. Another dimeric benzimidazole and bisbenzimide analog, targaprimir (TGP)-515, is UBAP2 promotes proliferation and inhibits apoptosis [168] MTO1 suppresses proliferation and invasion [171] identified to target pri-miR-515, resulting in up-regulation of human epidermal growth factor receptor 2 and enhancement of the therapeutic efficacy of the anti-human epidermal growth factor receptor 2 antibody in breast cancer cells [66]. Likewise, a bisbenzimide analog called targarpremir-210, also called TGP-210, is identified to bind to pre-miR-210, leading to the inhibition of processing of mature miR-210 and suppressing the outgrowth of xenograft tumors in mice [67].…”
Section: Targeting Ncrnas In Cancer Therapymentioning
confidence: 99%